2011
DOI: 10.1088/0964-1726/20/12/125002
|View full text |Cite
|
Sign up to set email alerts
|

The influence of thermal expansion of a composite material on embedded polarimetric sensors

Abstract: Abstract. Some of the most critical issues of the influence of the thermal expansion of composite materials on embedded polarimetric sensors for measurements of strain and temperature are studied in this paper. A composite material sample with polarimetric fiber sensors embedded in two distinct layers of a multi-layer composite structure is fabricated and characterized. The polarimetric fiber sensors used in this study are based on panda type fiber and polarization maintaining photonic crystal fiber (PM-PCF). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…The composite material sample is fabricated by using a hand lay-up method with glass fibre fabrics (E-glass) as the reinforcement and a general purpose unsaturated polyester resin as the matrix material [11][12][13]. The orientations of the glass fibres were unidirectional (0/0) to each other.…”
Section: Fabrication Of Composite Materials Sample With Embedded mentioning
confidence: 99%
See 2 more Smart Citations
“…The composite material sample is fabricated by using a hand lay-up method with glass fibre fabrics (E-glass) as the reinforcement and a general purpose unsaturated polyester resin as the matrix material [11][12][13]. The orientations of the glass fibres were unidirectional (0/0) to each other.…”
Section: Fabrication Of Composite Materials Sample With Embedded mentioning
confidence: 99%
“…However most of the studies were focused on the use of fiber sensors to measure the temperature and strain during the curing process and also during structural tests [7][8][9][10]. Our recent studies established that the thermal expansion effects of the composite material considerably affect the performance of the embedded sensors and result in a cross sensitivity in sensing parameters [11][12][13]. Therefore it is important to differentiate the influence of temperature of the composite material and thermal expansion induced effects on the embedded fiber sensor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific type of polarimetric sensor using micro-structured polarization maintaining highly-birefringent photonic crystal fiber (PM-HB-PC)F is proven to have very low temperature sensitivity in free space [20,21]. But we have shown that it acquires a significant response with temperature when embedded in a composite material, due to the stress-induced change in birefringence created by the thermal expansion of the composite material [22]. It is logical therefore to assume that this sensor could be used as a basis for measuring thermal strain and thus thermal expansion.…”
Section: Introductionmentioning
confidence: 99%
“…The fiber coating layer can be responsible for the behavior of the fiber inside a composite material [18]. The sidehole fiber was covered by a hard coating layer and transversal pressure was easily transmitted to the sensing fiber, introducing changes in its birefringence.…”
Section: Influence Of the Coating Layers Of The Optic Fiber On The Stmentioning
confidence: 99%